Revision of Megalothorax incertus Börner, 1903 reveals it to be another widespread Palearctic species of the genus (Collembola, Neelidae) - Schneider, Clément; Panina, Ksenia (Zootaxa, 2023)
Megalothorax incertus Börner, 1903 is the second species of Megalothorax to have been discovered. The brevity of the original description left the species insufficiently defined. In this work, we redescribe M. incertus from topotypes (Sicily) and describe a new species of the incertus-group: M. boerneri sp. nov. (France). We report the presence of M. incertus sensu nov. in France and Russia and validate a previous record from China based on molecular data. New records are also provided for a third species of the incertus-group, M. perspicillum Schneider & D’Haese, 2013. Novel DNA data (28S rDNA, 16S rDNA, COI) are provided for the three species. The interactive key of the Megalothorax species of the world is updated. The three species are distinguished on subtle morphological characteristics and are found to be well-separated on the molecular based phylogenetic tree. Megalothorax incertus sensu nov. joins M. perspicillum, M. minimus Willem, 1900 and M. willemi Schneider & D’Haese, 2013 in the club of widespread Megalothorax species in the Palearctic, and can be found in co-occurrence with them. Thus, the ecological distinction between those species remains unprecise.